Secured Group Data Bestow with Key-Agglomerative Searchable Encryption via Cloud Storage - Santhiya, C; Vanishree, KA; Chandrasekaran, MK (International Journal of Computer Sciences and Engineering, 2025)
The capability of distributing selected encrypted data with different users by means of public cloud storage may greatly alleviate the protection concerns over inadvertent data leaks in the cloud. Efficient management of encryption keys solves this difficulty. The preferred flexibility of distributing any group of selected documents with any group of users hassle different encryption keys to be used for different credentials. However, this also implies the requirement of securely sharing to users a large amount of keys for both encryption and search, and those users will have to securely stock up the received encrypted keys, and submit an equally large amount of keyword trapdoors to the cloud in order to carry out the exploration over the shared data. The obscure need for secure communication, storage, and complexity noticeably explains that the approach is not appliable. In this paper, a novel concept called, key aggregate Searchable encryption (KASE) is estimated to resolve this matter-of-fact problem and instantiating the notion through a concrete KASE scheme, in which a data holder only needs to share a single key to a user for distributing a large amount of documents, and the user only needs to tender a single trapdoor to the cloud for querying the user shared documents. But by using single key for a group, it is easily misused by the group members. If moved to multiple-keys, information is accesses by Brute-force attack. Hence it should be enhanced in a way that reduced number of keys should be used. The security analysis and concert evaluation both confirm that our projected schemes are provably secure and practically efficient.